1975: All in our time: A foul and awesome display. (1st November 2020) - Bainbridge, Kenneth T.
ABSTRACT: Kenneth Bainbridge recounts his role during the first nuclear bomb test in July 1945. This is the second and final installment of his account of the test. It also concludes a series of reminiscences of 12 nuclear pioneers begun in the Bulletin in April 1974.